Surgical aspects and results of a single-center prospective register of transcatheter aortic valve implantation - A. A. Prokhorikhin; A. A. Tarkova; D. D. Zubarev; E. I. Fartakov; D. U. Malaev; A. A. Boykov; O. V. Kamenskaya; E. I. Kretov (Российский кардиологический журнал)
Aim. To assess the results of transcatheter aortic valve implantation (TAVI) in patients with symptomatic aortic valve stenosis in routine clinical practice. Material and methods. From 2015 to 2018 based on the Meshalkin National Medical Research Center in the prospective register of patients undergoing TAVI, 191 patients were included. The patients were divided into low surgical risk group (EuroSCORE II <4%) — 137 patients, and increased surgical risk group (EuroSCORE II >4%) — 54 patients. We defined incidence of serious adverse cardiovascular events (allcause death, nonfatal myocardial infarction and nonfatal stroke/ transient ischemic attack (TIA)), as well as the incidence of permanent pacemaker implantation (PPI).Results. In the postoperative period, cardiac death was observed in 3 (2,2%) and 2 (3,7%) cases in the lowrisk and highrisk groups, nonfatal stroke/TIA — in 7 (5,1%) and 2 (3,7%) cases. The frequency of the composite endpoint was 10 (7,3%) and 4 (7,4%), respectively (p>0,999). During the hospitalization nonfatal myocardial infarction cases in the groups were not registered. The incidence of PPI due to the complete atrioventricular block was 10,9% and 13%, respectively.Conclusion. This prospective register demonstrates good results of TAVI in patients with different surgical risk. Relative frequency of lethality, nonfatal myocardial infarction, nonfatal stroke/TIA and PPI did not differ significantly in the low and high surgical risk groups.